Pengaruh Pemilihan Akun Media Sosial Instagram Terhadap Minat Berwisata Ke Korea Selatan - Rilo Dafa Prapiana, Zainal Abidin, Muhammad Ramdhani (Jurnal Mirai Management, 2023)
Technology at this time has such an important role, especially in everyday life. The rapid development of technology is one of them in the field of information and communication. The application that appeared also developed a lot of support for being able to communicate remotely. The application that is currently popular is Instagram. In this study, we will discuss how much influence the intensity of Instagram social media account selection has on the interest in traveling to South Korea on the Followers of tourkoreaid accounts. Then How much influence does the content of the Instagram social media account selection message have on the interest in traveling to South Korea on the Followers of the tourkorea.id account.In this study using quantitative methods by collecting data to distribute questionnaires, then the data was processed using simple linear regression analysis so that the truth and validity of the data were tested and with respondents totaling 100 people from followers @tourkorea.id. The results of the data analysis test showed that the influence of instagram social media selection on the interest in traveling to South Korea from followers @tourkorea.id based on 100 respondents obtained significant results as evidenced by table IV-9 rhitung 0.249 ≥ rtabel 0.163, so the hypothesis is accepted which can be interpreted that the influence of instagram social media account selection on the interest in traveling to South Korea from the @tourkorea.id account on its followers of 100 respondents significant value.travel needs in followers @tourkorea.id which numbered 100 respondents showed 0.89% which was of high value while the rest were results that showed not too much need to travel due to other factors outside this study. Keywords: Influence_1, Instagram_2, Travel_3